Comparison of Two Different Accesses Single Orifice Percutaneous Endoscopic Surgery in Diagnosis of Ascites of Unknown Origin: A Retrospective Study. (4th April 2022) - Guo, Li-liangzi; Wu, Ben-hua; Yu, Zhi-Chao; Luo, Ming-han; Li, Feng; Xiong, Feng; Wei, Cheng; Shi, Rui-yue; Liu, Ting-ting; Zhang, Ding-guo; Li, De-feng; Xu, Zheng-lei; et al.
Abstract : Background. Ascites is a common clinical finding caused by many different diseases, so we developed a technique termed single orifice percutaneous endoscopic surgery (SOPES) which can access peritoneal cavity through the contralateral McBurney's point or umbilicus to seek the underlying causes. In this study, we describe the initial clinical experience of SOPES and compare the application of two accesses. Methods. This is a retrospective study performed between 2007 and 2018. Patients with ascites of unknown origin who underwent these two kinds of SOPES were included. Main outcomes were measured by diagnostic accuracy, complication rate, procedure time, time till stitches removal, length of hospital stay, and hospital cost. Results. 148 patients successfully undergone SOPES via the contralateral McBurney's point (IM group, n = 70 ) or the umbilicus (UM group, n = 78 ). 63 patients in the IM group and 71 patients in the UM group reached clear diagnosis (90.0% vs. 91.0%, p = 0.831 ). The overall complication rate was 5.4%, while the UM group was higher than the IM group (10.3% vs. 0%, p = 0.017 ). All complications were resolved after medical treatment, and no mortality resulted from this procedure. The procedure time and the time until stitches removal in the UM group were longer than that in the IM group. There were no significant differences in length of hospital stay and hospital cost between the two groups. Conclusions. SOPES, which combines the strength of minimally invasive single orifice incision and flexible angles of examination and instrumentation, is a newly developed flexible endoscopic surgical modality that provides new important clinical valuable in evaluation of ascites of unknown origin. Moreover, SOPES via the contralateral McBurney's point was safer than the umbilicus approach.